UV-Initiated Polymerization of Cationic Polyacrylamide: Synthesis, Characterization, and Sludge Dewatering Performance - Huaili Zheng; Yongjun Sun; Xiaomin Tang; Mingzhuo Tan; Jiangya Ma; Wei Chen; Yong Liao (The Scientific World Journal, 2013)
P(AM-DAC-BA) was synthesized through copolymerization of acrylamide (AM), acryloyloxyethyl trimethyl ammonium chloride (DAC), and butylacrylate (BA) under ultraviolet (UV) initiation using response surface methodology (RSM). The influences of light intensity, illumination time, and photoinitiator concentration on the intrinsic viscosity [η] of P(AM-DAC-BA) were investigated. RSM model based on the influencing data was established for optimizing synthetic conditions. It was found that, at light intensity 1491.67 μw·cm−2, illumination time 117.89 min, and photoinitiator concentration 0.60‰, there was a better material performance achieved. Thus P(AM-DAC-BA) prepared under the above conditions showed excellent dewatering performance that, with 40 mg·L−1 P(AM-DAC-BA) at pH 7, the residual turbidity of supernatant and the dry solid content were up to 38 NTU, 28.5%, respectively.